A study to determine curriculum content for industrial arts in the junior secondary schools of Trinidad and Tobago - Dyer, Clifford V. (1974)
This study developed a curriculum guide for industrial arts education that was especially suitable to the new junior secondary schools of Trinidad and Tobago. Recent developments in vocational-technical education were studied and some observations and suggestions are made for its improvement. The study concluded that: 1) Trinidad and Tobago can benefit from those experiences that were obtained in the development of industrial arts education in the United States, 2) the new junior secondary schools of Trinidad and Tobago offered an opportunity to change and improve the methods of teaching industrial arts, and 3) the industrial arts curriculum project should be used as a pattern for such change in industrial arts education in the country. Included among the recommendations was that the teaching of industrial arts and science be very closely interrelated
Keywords: Junior secondary schools